Optimisasi Desain Rangka Bentor dengan Fokus pada Aspek Keselamatan Menggunakan Metode Pahl and Beitz - Aris, Muhamad Alfandi; Arafat, Muhammad Yasser; Lahay, Idham Halid (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study proposes a safer bentor frame design using a Research and Development (R&D) approach combined with the Pahl & Beitz design methodology. User requirements were gathered through field observations and questionnaires, revealing major safety issues in current bentor structures, including braking performance, suspension reliability, and dimensional inconsistency. A revised configuration was developed featuring a rear passenger layout, AISI 1020 frame material, front disc brake, telescopic suspension, and a differential drivetrain system. Structural performance was verified through static load simulation using Finite Element Analysis (FEA) based on real operating conditions. The results indicate a maximum stress of 140 MPa, displacement of 0.49 mm, and a safety factor of 2.49, remaining within the allowable limit of the material’s 351 MPa yield strength. These findings demonstrate that the proposed design offers improved structural integrity, stability, and operational safety, making it a viable alternative for practical implementation.